A "One Engine with Six Gears" System Engineering Methodology for the Economic Development of Unconventional Oil and Gas in China. (November 2022) - Li, Guoxin; Xian, Chenggang; Liu, He
Abstract: Unconventional oil and gas resources have become the most important and realistic field for increasing China's domestic oil and gas reserves and production. At present, the production scale does not match the massive amount of resources and the rapid growth of proven geological reserves. The challenges of technology, cost, management, and methodology restrict large-scale and economic development. Based on successful practices, a "one engine with six gears" system engineering methodology is put forward, which includes life-cycle management, overall synergy, interdisciplinary cross-service integration, market-oriented operation, socialized support, digitalized management, and low-carbon and green development. The methodology has been proved to be effective in multiple unconventional oil and gas national demonstration areas, including the Jimusar continental shale oil demonstration area. Disruptive views are introduced—namely, that unconventional oil and gas do not necessarily yield a low return, nor do they necessarily have a low recovery factor. A determination to achieve economic benefit must be a pervasive underlying goal for managers and experts. Return and recovery factors, as primary focuses, must be adhered to during China's development of unconventional oil and gas. The required methodology transformation includes a revolution in management systems to significantly decrease cost and increase production, resulting in technological innovation.